PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Debi Monika, Ni Gusti Ayu Putu; Sudjarni, Luh Komang (E-Jurnal Manajemen, 2018)
The dividend d. policy concerns the issue of the use of profits which are the rights of shareholders, the profits may be divided as dividends or retained for reinvestment. This study aims to determine the effect of liquidity, profitability, and leverage on dividend d. policy on om manufacturing companies listed on the Indonesia Stock Exchange period 2011-2015. The population in this study is a manufacturing g. company which amounted to 144 companies. The sampling technique used is s. purposive sampling so as to get as many as 15 sample company at manufacturing g. company. Data collection method used in the research is non participant observation, with data in the form of financial statements obtained from www.idx.co.id. The data analysis technique used is multiple linear regression. Based on the results of the analysis sho w w. that partially liquidity and profitability significantly positive effect on dividend d. and leverage policies have a significant negative effect on dividend d. policy on m manufacturing companies in Indonesia a Stock Exchange period 2011-2015. Keywords : Liquidity, Profitability, Leverage, Dividend Policy